Development of Water Quality Index for Coastal Zone and Application in the Hạ Long Bay - Nguyên, Nguyễn Thị Thế; Loan, Đồng Kim; Hồi, Nguyễn Chu (VNU Journal of Science: Earth and Environmental Sciences, 2013)
Abstract: In this study , a water quality index (WQI HL ) was developed in accordance with the nature of coastal zone and applied to assess the water quality in Ha Long Bay .  Nine parameters, including %DO sat (0.08), COD (0.11), TOC (0.08), oil and grease (0.17) total coliforms or feacal coliform (0.07), TSS (0.17), TN or NH 4 + (0.11), TP or PO 4 3- (0.11) and chlorophyll a (0.11) are employed for the estimation of water quality . Numbers in the parentheses indicate weight of each parameter. Sub-indices are built based on the QCVN 10:2008/MONRE, the standards on coastal water quality of ASEAN, Australia, Japan … and other requirements for w ater quality in marine ecosystems . Assessment of the eclipsing and ambiguous effects and the sensitivity of four aggregation functions reveal that weighted geometric mean function is the most appropriate to calculate WQI HL w ith selected weights . The application of the developed WQI HL in the Hạ Long Bay shows that water quality in the core zone is good, except some tourist areas and fishing villages. The buffer zone of the Bay possesses poor water quality. The WQI HL formula can be a good tool for water quality management and planning, which supports for the integrated coastal zone management. Keywords : Water quality index, weighted geometric mean function, coastal zone, Hạ Long Bay .